Sistem Pakar Diagnosis Penyakit Gastritis Menggunakan Metode Certainty Factor Berbasis Android - Windarto, Yudi Eko; Isnanto, R Rizal; Setiawan, Annas (Jurnal Transformatika, 2020)
With the increasingly of the modern era, more and more diseases that arise due to human lifestyle and bacterial transmission. One of them is gastritis which occurs because of inflammation that occurs in the lining of the stomach which makes frequent pain in the stomach. From these problems, it is necessary to make an expert system application of gastritis disease which aims to provide information to the public to know the early symptoms of gastritis from an early age. The process of diagnose using the certainty factor method The methods in this study are data retrieval, system design, system making and system testing.From this research, it produces an expert system application that can diagnose the type of disease with the first test case 98.848%, the second test case 99.8464% and the third test case with the results of 99.99115264% correct and in accordance with expert knowledge. System testing is done by using black-box testing that shows the function of each unit of application 100% successful.